Strategi Komunikasi Interpersonal Unit Pengelola Sampah Terhadap Mahasiswa Sebagai Upaya Meminimalisasi Sampah Di Universitas Trunojoyo Madura - Tirtoaji, Wahyu; Nedisa, Violina; Wahyono, Amin; Qatrunada, Nasywa; Rahmawati, Andinia; Anatika (Universitas Cokroaminoto Yogyakarta, 2024)
Waste management in higher education is an important issue that needs serious attention, especially at Trunojoyo University Madura which is often faced with waste problems. One of the factors causing it is the low awareness of students to dispose of garbage in its place. This study aims to analyze the interpersonal communication strategy of the Waste Management Unit in making efforts to minimize waste at Trunojoyo Madura University. One of the factors is student awareness and the lack of trash can facilities on campus. This research uses a descriptive qualitative approach through observation and interviews. Through an effective interpersonal communication strategy, it is expected to encourage changes in behavior that are more concerned about waste. The results showed that Trunojoyo Madura University produces 3 to 4 full garbage carts per day and even when Trunojoyo Madura University holds events both internally and externally the garbage produced reaches 4 full pick-ups.